2021
DOI: 10.1038/s41598-021-96154-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of women’s weight trajectories in determining familial cardiovascular disorders: a family-based longitudinal study

Abstract: Considering the dynamic nature of body mass index (BMI) and its importance in determining cardiovascular risks, this study aimed to investigate the life-course trajectory pattern of women’s BMI and its association with cardiovascular risk factors. A total of 1356 couples with 2976 children were recruited and followed up for an average period of 20 years. Latent growth curve modeling was applied to determine women's BMI trajectories; logistic regression was used to investigate the associations between trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This condition is characterized by the thickening MACCEs [17]. Hypertension can significantly increase the risk of cerebral hemorrhage, and diabetes is also a risk factor for vascular diseases [18,19]. The concurrent presence of hypertension and diabetes can greatly increase the risk of MACCEs in uremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is characterized by the thickening MACCEs [17]. Hypertension can significantly increase the risk of cerebral hemorrhage, and diabetes is also a risk factor for vascular diseases [18,19]. The concurrent presence of hypertension and diabetes can greatly increase the risk of MACCEs in uremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes are more prone to developing MACCE [16]. Hypertension has been proven to be a cardiovascular risk factor [17]. Other studies have shown that diabetes increases the risk of vascular diseases [13].…”
Section: Discussionmentioning
confidence: 99%
“…After excluding 141 duplicates and 8,160 unrelated articles based on screening of the title and abstract, 112 full-text publications were reviewed for eligibility. Ultimately, 18 articles provided sufficient information and were considered qualified for our meta-analysis (6,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The 18 cohort studies included 89,094 participants.…”
Section: Study Selectionmentioning
confidence: 99%